The role of developmental assets for prosocial behaviours among adolescents in Malaysia - Kaur, Amrita; Yusof, Norhafezah; Awang Hashim, Rosna; Ramli, Romlah; Dalib, Syarizan; Mohd Sani, Mohd Azizuddin; Mat Isa, Nasharudin (Elsevier Ltd, 2019)
Development of prosocial behaviours among adolescents is a valuable goal of any society. Using a cross-sectional survey design, the current study explored the role of external (school/university, friends and family, and community engagement) and individual developmental assets (purpose in life and cognitive autonomy) in explaining the development of prosocial behaviours among adolescents in Malaysia. A sample of 324 first year undergraduate students from two public universities in the north of Malaysia participated in the study. The data was analysed using structural equation modeling in AMOS 23 to test the hypothesised relationships. The results suggested that cognitive autonomy is predicted by community engagement and friends and family only whereas purpose in life was predicted by school/university, friends and family, and community engagement which in turn predicted prosocial behaviours among the adolescents. Implications for strengthening developmental assets are highlighted.